Ionic conductivity of PVDF-HFP/MG49 based solid polymer electrolyte - Ataollahi N.; Ahmad A.; Hamzah H.; Rahman M.Y.A.; Mohamed N.S. (2023)
Blend-based polymer electrolytes composed of PVDF-HFP/MG-49 (70/30) and LiClO 4 as lithium salt has been studied. Solution casting method was applied to prepare the polymer electrolyte. Electrochemical impedance spectroscopy (EIS) and Fourier transform infrared spectroscopy (FTIR) were used to characterize the electrolyte films. The maximum value of 2.5110 -6 S cm -1 was obtained at ambient temperature for the 30 wt. % of LiClO 4 and the conductivity increased to 1.1010 -3 S cm -1 by increasing the temperature up to 383 K. FTIR spectra demonstrated that complexation occurred between the polymers and lithium salt. (2012) Trans Tech Publications.